Supporting Communities in Transition : The Impact of the Armenian Social Investment Fund - Chase, Robert S. (Washington, DC: World Bank, 2014)
The Armenian Social Investment Fund supports communities' efforts to improve local infrastructure during Armenia's economic transition away from central planning, financing community-designed and -implemented projects to rehabilitate primary schools, water systems, and other infrastructure. This article considers the targeting, household impact, and community effects of the social fund's activities. It relies on a nationally representative household survey, oversampled in areas where the social fund was active. Using propensity and pipeline matching techniques to control for community self-selection into the social fund, it evaluates the household effects of rehabilitating schools and water systems. The results show that the social fund reached poor households, particularly in rural areas. Education projects increased households' spending on education significantly and had mild effects on school attendance. Potable water projects increased household access to water and had mild positive effects on health. Communities that completed a social fund project were less likely than the comparison group to complete other local infrastructure projects, suggesting that social capital was expended in these early projects. By contrast, communities that joined the social fund later and had not yet completed their projects took more initiatives not supported by the social fund.